Anatomical Post In Crown Fractures With Composite Direct Restoration: A Case Report - Nur’aini Badriah; Trimurni Abidin; Widi Prasetia (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
Crown fractures in maxillary incisors, particularly complicated crown fractures, present significant clinical challenges due to their impact on aesthetics, function, and the psychological well-being of patients. The management of such fractures often requires a multidisciplinary approach involving endodontics and orthodontics, to achieve optimal outcomes. This case report aim to give recommendation treatment for crown facture with gross loss structure and malposisition. A 18 years old male patient arrived to Dental Hospital( RSGM USU) with chief complain his upper front teeth fracture three years ago. Negative vitality tests and no mobility. Periapical radiographs indicated apical resorption. Diagnose for 11 and 21 is Pulp Necrosis with Asymptomatic Apical Periodontitis. Anterior teeth were crowded and need orthodontic treatment. Anatomical post used in 11, 21 with extensive loss of hard tissue structure to support final restoration. Anatomical post not only enhance aesthetics but also used in endodontically treated teeth to correct the teeth inclination. The advantages of anatomical post made of polyethylene fibre include aesthetic, bond well with tooth structure, and elastic modulus close to dentin. Direct composite restoration aims to placement of orthodontic appliances to correct malocclusion and orthodontic extrusion is necessary to restore the biologic width and achieve proper aesthetics in this case. Direct composite restorationis necessary for correcting malocclusion using orthodontic appliances to support the successfull treatment.